A carbonized carbon dot-modified starch aerogel for efficient solar-powered water evaporation. Issue 21 (17th May 2022) - Xu, Xiaoshi; Chang, Qing; Xue, Chaorui; Li, Ning; Wang, Huiqi; Yang, Jinlong; Hu, Shengliang
Abstract : A new low-cost and eco-friendly solar evaporator made of a carbonized carbon dot-modified starch aerogel (C-CDSA) with a high solar energy conversion efficiency and excellent stability and durability was developed for solar-powered water evaporation. Abstract : Solar-powered water evaporation shows prominent advantages in extracting fresh water. To achieve high photothermal-conversion efficiency, development of efficient solar evaporators is highly pursued. Here, a new solar evaporator made of a carbonized carbon dot-modified starch aerogel (C-CDSA) was developed. Benefiting from the introduced carbon dots (CDs) that promoted the polymerization and carbonization of starch chains, C-CDSA exhibited a three-dimensional (3D) interconnected porous structure with a larger pore size and thinner pore wall as well as higher porosity. Due to the low carbonization temperature (270 °C) and the feature of CDs with rich oxygenated groups, a higher content of oxygenated groups was preserved in C-CDSA, which not only ensured the super hydrophilicity but also contributed to water activation. By virtue of the structural and compositional advantages, C-CDSA showed enhanced light harvesting, desired thermal insulation, fast water transportation and superiority in reducing the water evaporation enthalpy. Therefore, the designed low-cost and eco-friendly C-CDSA not only exhibited a high evaporation rate of 2.29 kg m −2 h −1 with an energy conversion efficiency of 93.5% under 1.0 sun irradiation, but also showed stable water evaporation performance in acidic, alkaline, high-salt (10 wt%) and organic pollutant solutions, holding great promise for practical solar water evaporation applications.